An illustrated catalogue of the types of Stratiomyidae (Diptera: Brachycera) in the collection of Museu Nacional, Rio de Janeiro, Brazil - Fachin, Diego Aguilar; Couri, Márcia Souto; de Mello-Patiu, Cátia Antunes (Zootaxa, 2016)
A catalogue of the type specimens of Stratiomyidae (Diptera: Brachycera) held in the collection of Museu Nacional, Rio de Janeiro, Brazil (MNRJ) is presented. A total number of 50 type specimens of 18 valid Neotropical species were recognized and are listed in alphabetical order of subfamily, genus and specific epithet. Photos of 12 primary types of the species and bibliographical data of the original descriptions, labels and condition of all type specimens are also provided.